KOLABORASI PENELITI DI ERA TEKNOLOGI INFORMASI DAN KOMUNIKASI - Febrian Rusdi, Jack; Gurat Baktina, Tedja; Gumilar Hadiningrat, R.; Sunaryo, Budi; Laurenty, Fretycia (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
Advances in information and communication technology have an impact on increasing the number ofscientific publications in the world. Scientific papers are an indicator of a country's progress in theacademic field. One strategy used to improve the quality of scientific publications is throughcollaboration between researchers. From various study result searches, there are not many studies thatdiscuss the collaboration of researchers. The purpose of this study is to produce one of the fundamentalstudies on research development in Indonesia. The method used in this study is the study of literature.This article contributes to the collaboration picture of researchers, including the background ofcollaboration and aspects that affect collaboration, as well as the contribution of Indonesian research interms of information technology to support research for researcher.